Paediatric urologic pathologies at the national teaching hospital in Cotonou: A etiological and therapeutic aspects - Augustin Karl Agossou-Voyeme; Michel Armand Fiogbe; Judith Goundete; Gervais Martial Hounnou; René Hodonou (Wolters Kluwer Medknow Publications, 2013)
Background: Urological pathologies of children are dominated by congenital malformations of the kidneys and urinary tract. Their management is often surgical. The objective of this survey was to study etiological and therapeutic aspects of urological presentations in children. Patients and Methods: Data for aetiology, treatment, and results in children hospitalized at the Paediatric Surgery service of National Teaching Hospital (CNHU) in Cotonou were retrospectively analyzed from January 1999 to December 2008. Results: A total of 214 patients with complete data were evaluated. Urological pathologies represented 4.8% of the hospitalizations in paediatric surgery, with an incidence of 21 cases per year. The mean age was 4.9 ± 3.2 years (age 1 week to 14 years). The male to female ratio was 14:14. Cryptorchidism, hydrocele, nephroblastoma, the posterior urethral valves, ureteropelvic junction obstructions, post-circumcision haemorrhage and hypospadias were the most frequent pathologies. Congenital urological malformations represented 81.3%, followed neoplastic pathologies (7.9%), traumatic pathologies (6.1%) and others (4.7%). The disorders of male genitalia were more frequent and constituted 68.2% of the cases. The anomalies of the urinary tract were 30.8% and intersex disorders were 0.9%. The average age of the children urological pathologies at the time of consultation was 8.85 ± 4.6 years. The treatment was often surgical with a mortality of 2.8%.